Analisis dan Mitigasi Risiko dalam Pengadaan Menggunakan Pendekatan House of Risk pada Perusahaan Jaringan Broadband - Divazanna Illaritzqi; Silvi Istiqomah; Abduh Sayid Albana (Pusat Riset dan Inovasi Nasional, 2024)
In 2023, the number of internet users in Indonesia significantly increased to 212.9 million, highlighting the importance of reliable network infrastructure. A broadband network company operating in the telecommunications sector faces various risks in its procurement process of materials and services that are essential to support its operations. Risks such as material delays and specification mismatches present challenges that must be carefully managed. This study employs the House of risk (HOR) method to analyze 19 risk agents and risk events that could potentially impact the procurement process, focusing on five primary risk agents. The proposed preventive actions, particularly through effective communication, are expected to mitigate the impact of risks in the procurement process within the broadband network company.